Unlocking the Inventive Potential of Knowledge Distance in Teams: How Intrateam Network Configurations Provide a Key - Vestal, Alex; Danneels, Erwin (Organization Science, 2024)
Increasingly, teams consist of members from widely distinct knowledge domains. This article studies the extent to which research and development (R&D) teams can transform their members’ different technological knowledge into impactful inventions. Although teams composed of members with distinct expertise can create impactful new technologies, in order to realize this potential, team members must have the ability and motivation to integrate each other’s knowledge. This article argues that the ability to do so is shaped by the patterns of intrateam ties, measured in terms of coauthorships on patents. Our results suggest that teams’ ability to reap the advantages of members’ distinct expertise is shaped by the patterns of members’ prior collaboration ties. Prior experience working together (i.e., density) and the presence of factions of team members with common history (i.e., subgroups) improve teams’ ability to leverage differences in members’ knowledge. In contrast, when prior collaborations center on one focal person (i.e., centralization), teams are less able to take advantage of the knowledge differences on the team. An analysis of 32,612 nanotechnology R&D teams provides support for the hypotheses. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2023.1665 .